Rapid-printed Three-dimensional Models for Craniomaxillofacial Trauma - Isabel M. Scharf, BA; Sydney A. Mathis, BS; Naji Bou Zeid, MD; Devansh Saini, PhD; George R. Nahass, BA; Eduardo Arias, BFA, MSc, CCA; Chad A. Purnell, MD; Linping Zhao, PhD; Pravin K. Patel, MD; Lee W.T. Alkureishi, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Advances in surgical planning and 3-dimensional (3D) printing have benefitted the field of craniomaxillofacial surgery by allowing visualization of patient anatomy in settings of otherwise restricted surgical fields. Long 3D print times limit the usability of surgical planning workflows in acute trauma reconstruction. We sought to identify variables affecting print time and produce rapid-printed models with sufficient quality for prebending osteosynthesis plates. Methods:. Three-dimensional printing variables, including resolution, print orientation, and region of interest cropping, were optimized on a single mandibular and midface fracture model to maximize print time efficiency. Five mandibular and 5 midface fractures were printed both in the high-resolution and time-efficient protocol. Fixation plates were contoured to fit the optimized models and computed tomography scan. Distances and volumes between the fracture surface and plate were computed. Results:. High-resolution mandible models were printed in 7.47 hours and maxillae in 7.53 hours. Optimized models were printed in 0.93 and 1.07 hours, respectively. Cropping to regions of interest, rotating the model, and decreasing print resolution significantly reduced print time. The difference (optimized versus high resolution) in distance between the plate and model averaged 0.22 and 0.34 mm for mandibles and maxillae; the air space volume differed by 1.39 and 0.90 mm3, respectively. Conclusions:. Adjusting size, resolution, and position on the printing platform allows rapid fabrication of 3D models for surgical reconstruction without sacrificing surface quality. These edits reduce printing time, enabling the implementation of 3D-printing workflows for surgical planning in acute craniomaxillofacial trauma settings.